Study on Supercritical CO2 Heat Transfer Enhancement in Airfoil PCHE - Xiaojun LIAN; Li ZHANG; Fei WANG; Gang LI; Yue GAO; Wenquan JIANG (Liaoning Shiyou Huagong Daxue xuebao)
In order to break through the bottleneck of heat transfer efficiency of traditional printed circuit heat exchangers, a physical model of airfoil PCHE was established, numerical simulations were conducted to study the convective heat transfer of supercritical CO2 in the model, the heat conduction principles of supercritical CO2 under varying mass flow rates and inlet temperatures have been analyzed, and by changing the hydraulic diameter of the channel, further study the heat quantity transfer situation. The results indicate that the thermal exchange performance can be improved by increasing the mass flow rate and the inlet temperature of the cold fluid. At varied hydraulic diameter of the passage, the heat transfer capacity of PCHEs with chord lengths of 6 mm and 8 mm both increase with the increase of Reynolds number. When the Reynolds number is between 19 500 and 26 000, PCHEs with chord lengths of 6 mm and 8 mm have similar heat transfer performance; when the Reynolds number is between 26 000 and 50 000, the comprehensive performance of PCHE with a chord length of 8 mm is 2.55% higher than that of PCHE with a chord length of 6 mm. The research results provide a theoretical basis for the structural design of airfoil PCHE.